MEAN TIP-APEX DISTANCE IN LAG SCREW CUT-OUT AFTER DYNAMIC HIP SCREW FIXATION OF HIP FRACTURE - Shabir, Muhammad; Inam, Muhammad; Awan, Abdus Saboor; Kamran, Faisal; Ahmad, Nehal (Journal of Ayub Medical College Abbottabad, 2018)
Background: To determine mean tip-apex distance after Dynamic Hip Screw fixation of intertrochanteric fracture. Methods: Descriptive Cross-sectional study was conducted in the Department of Orthopaedics, Hayatabad Medical Complex, Peshawar from October 2015 to September 2016 on a total 285 patients. Results: A total of 285 patients were observed. Status of TAD among 285 patients was analysed as 171 (60%) patients had TAD ranged 15 mm to 20 mm, 91(32%) patients had TAD ranged 21 mm to 25 mm, 23 (8%) patients had TAD ranged >25mm. Mean TAD was 18 mm with SD±7.45. Eight percent patients had screw cut out while 92% patients didn’t had screw cut out. Conclusion: To avoid lag screw cut out in dynamic hip screw for intertrochanteric fracture of hip the Tip apex distance must be accurate otherwise there will be cut out of lag screw. Keywords: Tip-Apex Distance; Lag Screw Cut-Out; Dynamic Hip Screw; Intertrochanteric fracture